Comparison of countries in the WHO European Region according to noncommunicable disease indicators by multi-criteria decision making methods - Bulut, Tevfik (Acta Medica, 2025)
Objective: The aim of this study is to compare the relative risk prevalence of noncommunicable diseases (NCDs) in the countries of the European Region as defined by WHO (World Health Organization) using WASPAS (Weighted Aggregated Sum Product Assessment) and MULTIMOORA (Multi-Objective Optimization by Ratio Analysis plus the full Multiplicative Form) multi-criteria decision-making (MCDM) methods. Materials and Methods: The cross-sectional study’s target population consisted of 50 countries in the WHO European Region with complete observations. The study utilizes NCDs data that the WHO publicly released. Analysis was performed using the R programming language and Microsoft Excel. Results: Based on the CRITIC (CRiteria Importance Through Intercorrelated Corrected) weighted WASPAS analysis, it was observed that 24 European countries exhibited Q scores above the average, while 26 countries displayed Q scores below the average. Finland, Cyprus, Switzerland, Spain, Iceland, Iceland, Sweden, Slovenia, Italy, Norway, Latvia, Portugal, Luxembourg, Belgium, France, Greece, the Netherlands, Germany, Malta, Austria, Ireland, Israel, Lithuania, Israel, Lithuania and Estonia have the highest Q scores. Twenty-four countries with above-average Q scores have lower NCD prevalence than twenty-six European countries. In Türkiye, the prevalence of NCDs is above the European average. However, Switzerland, Finland, Iceland, Spain, Cyprus, Slovenia, Sweden, Portugal, Norway, and Luxembourg are among the top 10 European countries with the lowest NCD prevalence in the overall MULTIMOORA ranking. According to the overall ranking, Turkmenistan, Tajikistan, and Kyrgyzstan have the highest NCD prevalence. Conclusions: The findings from the CRITIC based WASPAS method and the CRITIC based MULTIMOORA indicate that the prevalence of NCDs generally varies according to income level. Higher-income countries note a lower prevalence of NCDs compared to those with lower income levels. Nonetheless, the prevalence of NCDs may differ among various socioeconomic groups.